The perceptions of mainstream teachers, special class teachers and special needs assistants regarding the inclusivity of special classes for children with Autism. - Duggan, Emma (Marino Institute of Education, 2021)
Over the last few decades, Inclusive Education has become a prominent topic of discussion in Ireland and around the world. Unfortunately, inclusion remains an ambiguous term and as such, what forms of education provision can be classified as inclusive has been widely debated. In Ireland, children with Autism Spectrum Disorder (ASD) are educated in mainstream classes with the support of a Special Needs Assistant (SNA), in a special class attached to a mainstream school or within a special school itself. Many researchers have questioned the inclusivity of the special class model in Ireland and, in 2019, the National Council for Special Education (NCSE) announced a review of special education provision in Ireland, with the suggestion of a possible move towards full inclusion in mainstream for all children with special educational needs (SEN). The aim of the present study was to investigate the perceptions of mainstream teachers, special class teachers and SNAs in relation to the inclusivity of special classes. A qualitative research paradigm and case study design were chosen for the investigation. Interviews were conducted with seven participants about their perspectives and experiences with Inclusive Education for children with ASD in a primary school. Findings demonstrated the elusive nature of the term ‘inclusion’ but showed that participants believed inclusion to be a benefit to neurotypical peers in mainstream classes. A number of challenges to inclusion were also highlighted by the participants. The majority of participants felt special classes were beneficial to the children with ASD but a few expressed concerns about the segregated setting and lack of integration. All participants believed that it was imperative to provide a range of options to parents and children to enable them to find the best fit in terms of education setting for their child and their individual needs.
Keywords: Inclusive Education; Autism Spectrum Disorder (ASD); Special Needs Assistant (SNA); National Council for Special Education (NCSE); Special educational needs (SEN).; Ireland; Education; Inclusion (Education); Inclusive learning